Coloured and low conductive fabrics by in situ laccase-catalysed polymerization - Su, Jing (2019)
Coloured and conductive fabrics were obtained through in situ laccase polymerization of catechol and p-phenylenediamine under high-pressure homogenization. Both monomers, catechol and p-phenylenediamine, were polymerized by different laccase forms, namely native, PEGylated and Epoxy-PEGylated. All the catalysts were placed inside a textile fabric bag which served simultaneously as enzyme support and as substrate for coating with the newly produced polymers. The PEGylated laccase forms gave rise to higher amount of oligomers/polymers and higher colouration level of polyethylene terephthalate (PET), cotton and wool fabrics compared to native laccase. Both functional polymers were able to confer conductivity to the substrates however in a different extent. Fabrics coated with poly(p-phenylenediamine) present higher conductivity, rather due to its polymerized structure than to the amount of polymer produced by enzyme catalysis. Herein a green approach was presented to produce polyphenols with increased fixation onto different textile substrates. These substrates reach high levels of colouration and good fastness behaviour after washing.